Protagonismo Estudantil em Escolas Estaduais de Educação Profissional - Souza, Camila Maria Cunha de (2017)
This master thesis aims to investigate student protagonism in the State Schools of Professional Education (EEEP) in Fortaleza, drawing a parallel between the reality of students of this type of teaching and students of regular schools. The professional schools have a number of particularities when compared to regular schools, such as: they are full - time, students attend high school integrated to technical education and attend mandatory training. These particularities make them an intriguing object and field of research. It is necessary to present a brief history of professional education in Brazil, since this modality of teaching has been used since the colonial period in several contexts. The bibliographical survey focuses on the concepts of youth and protagonism. Qualitative and quantitative methodological tools were adopted in order to achieve more comprehensive results. The first part of the research consists of observations, interviews and focus groups carried out in an EEEP located in a suburb of Fortaleza - CE. Later, 1300 questionnaires were administered to students of ten schools in the same city, five of which were professional and five were regular. From the questionnaires‘ data, it was possible to create and measure indexes of protagonism among students and compare those from EEEPs with the ones from regular schools. The conclusion is that being a student of a professional school has a positive effect on the indexes of protagonism.